The methods of court supervision in the stage of preliminary investigation - Ахмедов, В. А. (Problems of legality, 2014)
Provided article tells about the methods of court supervision in the stage of preliminary investigation. It depends on the role of court on the place of law-enforcement organs in the stage of preliminary investigation providing lawfulness and fundamental of being criminal-procedural activities. In this article the author based upon scientific evidence and practical side of the need for court supervision, role of court and gave their suggestions to Code of Criminal Procedure of Azerbaijan Republic.